Procurement of goods and services by international organisations in donor countries - Gilles Carbonnier (Revue Internationale de Politique de Développement)
This article examines the procurement of goods and services by multilateral organisations from suppliers, based on a panel data including industrialised countries and emerging economies over 11 years. It presents the results of an empirical study – the first of its kind – on the explanatory factors of variations between countries, which are mainly attributable to such factors as the strength of the manufacturing sector and business ties established in the past. The results seem to indicate that the contributions paid by donor countries may have a positive influence on the procurement of goods and services, despite the fact that multilateral organisations purchase goods and services through international tendering procedures. Geographical proximity, cultural and linguistic affinities and the presence of the headquarters of a multilateral organisation in the country also play a positive role. The purchase of goods and services by multilateral agencies may be considered as an indirect effect of official development assistance (ODA). With many donor countries facing serious economic and budgetary constraints, documentation of the “return on investment” may serve as a means of encouraging policymakers to increase – or at least to not reduce – ODA budgets, including for multilateral agencies. Such arguments must nevertheless remain marginal with respect to the key debates on aid effectiveness and on on the performance of multilateral organisations.